Near-fields of an array of circular-loop antennas - Hamed, Sameir M. Ali; Abdulwaheed, Musa; Bashir, Saad Osman (IEEE, 2013)
In this paper an exact electromagnetic near-fields expressions for an array of circular loop antennas (CLA) are presented. The technique is based on the spherical wave functions expansion for the free space Green’s function. Fields of the uniform current CLAs array and that on the axis of the array, as well as the fields of the so called gate antenna arrangement, are obtained from the general expressions as a special cases. The known far-field expressions for the array of CLAs are derived from the general expressions which check the correctness of these general field expressions.